ENHANCING PUBLIC SERVICE DELIVERY "TEMAN PBB” APPLICATION WITH INSIGHTS FROM SOUTH KOREA - Dwiputrianti, Septiana; Agatha, Jessica; Wirjatmi T.L, Endang; Lee, Hye Kyoung (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service initiative aims to enhance public awareness of the importance of paying Land and Building Tax (PBB) through the use of the digital application Teman PBB, launched by the Bandung City Government. The selection of South Korea as a reference country for this application is based on its renowned reputation for technological innovation and the successful implementation of effective e-governance systems. By adopting best practices from South Korea, it is anticipated that the Teman PBB application will significantly improve the quality of public services, particularly in terms of efficiency and transparency. The methodology employed in this initiative includes outreach and direct assistance to neighborhood heads (RW) and residents in Bandung City. The community service approach is concentrated in the Cihaurgeulis Sub-district, encompassing the stages of planning, implementation, and evaluation. Activities include socialization efforts aimed at increasing taxpayer awareness through direct engagement and the distribution of informational materials. Quantitative and qualitative data will be collected to measure the success of this program, including the increase in application users and feedback from the community regarding their experiences with the application. The results of this initiative indicate that the implementation of the Teman PBB system not only simplifies the tax payment process for citizens but also raises public awareness of the importance of digital technology in tax administration. Despite certain challenges—such as limited access for iOS users—collaboration with South Korean academics is expected to provide innovative solutions to enhance the inclusivity and effectiveness of the application. Consequently, this initiative not only elevates public awareness but also makes a tangible contribution to the development of technology-based public services in Bandung. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kesadaran masyarakat akan pentingnya membayar pajak bumi dan bangunan (PBB) melalui pemanfaatan aplikasi digital Teman PBB yang diluncurkan oleh Pemerintah Kota Bandung. Pemilihan Korea Selatan sebagai negara referensi dalam pengembangan aplikasi ini didasarkan pada reputasinya dalam inovasi teknologi dan keberhasilan implementasi sistem e-governance yang efektif. Dengan mengadopsi praktik terbaik dari Korea Selatan, diharapkan aplikasi Teman PBB dapat meningkatkan kualitas layanan publik secara signifikan, terutama dalam hal efisiensi dan transparansi. Metode yang digunakan dalam kegiatan ini adalah sosialisasi dan pendampingan langsung kepada Ketua RW dan warga di sekitar Kota Bandung. Pendekatan ini difokuskan pada Kecamatan Cihaurgeulis, melalui tahapan perencanaan, pelaksanaan, dan evaluasi. Kegiatan tersebut meliputi sosialisasi untuk meningkatkan kesadaran wajib pajak melalui keterlibatan langsung dan distribusi materi informasi. Data kuantitatif dan kualitatif akan dikumpulkan untuk mengukur keberhasilan program ini, termasuk peningkatan jumlah pengguna aplikasi dan umpan balik dari masyarakat terkait pengalaman mereka dalam menggunakan aplikasi. Hasil dari kegiatan ini menunjukkan bahwa penerapan sistem "Teman PBB" tidak hanya menyederhanakan proses bagi wajib pajak, tetapi juga meningkatkan kesadaran publik terhadap pentingnya teknologi digital dalam pembayaran pajak. Meskipun terdapat beberapa kendala, seperti keterbatasan akses bagi pengguna iOS, kolaborasi dengan akademisi Korea Selatan diharapkan dapat memberikan solusi inovatif untuk meningkatkan inklusivitas dan efektivitas aplikasi. Dengan demikian, kegiatan ini tidak hanya meningkatkan kesadaran masyarakat, tetapi juga memberikan kontribusi nyata terhadap pengembangan pelayanan publik berbasis teknologi di Bandung.